Rebranding Agen Travel "Jajantiket" Melalui Perancangan Identitas Visual Untuk Meningkatkan Brand Awareness - Maulida, Laila; Joselin, Rachel Florencia; Rizkizha, Ditya Fajar (Jurnal Desain Komunikasi Visual Asia, 2024)
Jajantiket is a travel agent that focuses on selling plane tickets and sailing trips to Labuan Bajo, East Nusa Tenggara. This company, which is domiciled in Yogyakarta, has been operating for 5 years in the tourism industry sector. Competitive business competition requires Jajantiket to change its strategy in strengthening its image in the minds of consumers, one of which is by redesigning its visual identity. Currently Jajantiket only has a logo and visual identity design which is still inconsistent and has not been comprehensively planned. Therefore, it is necessary to design a visual identity for Jajantiket so that it can be well received by the audience, giving the impression of being professional, trustworthy and providing the best service to consumers. This design uses the Robin Landa method with five stages, Orientation, Analysis, Conception, Design, and Implementation. The data collection technique was carried out using a qualitative descriptive method and analysis used the S.W.O.T method. This design produces the Jajantiket logo and its application in related media, such as mascots, supergraphics, and its implementation in other media.